Risk Mitigation Strategies for Creative Batik Manufacturing Supply Chains Using the House of Risk Method and Supply Chain Operations Reference - Nurul Ummi; Atia Sonda; Indiani (Politeknik APP Jakarta, 2026)
The batik supply chain faces several risks, including transportation errors, unpredictable weather, and human errors, which can disrupt operations, reduce efficiency, and weaken competitiveness. This study aims to identify risk events and risk agents in the batik supply chain, prioritize key risk sources, and propose mitigation strategies. The study integrates the Supply Chain Operations Reference (SCOR) and House of Risk (HOR). Priority risks include transportation mode errors, unpredictable weather, sudden order increases, human errors, and room temperature changes. Seven mitigation actions were proposed, including establishing expedition contracts, applying First-in-First-Out order prioritization, and providing regular worker training, prioritized by effectiveness-to-difficulty ratio, with the highest at 1984,5. This study contributes to supply chain risk management literature by applying the SCOR–HOR framework to traditional craft-based SMEs and highlighting the influence of worker skills, environmental uncertainty, and supplier dependency on supply chain risks.